Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Produk Susu Bearbrand di Palembang - F, Ferdinand (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of product quality and brand image on the purchase decision of Bear Brand dairy products in Palembang City. This study uses a quantitative approach with a type of causal associative research. Data was collected through a questionnaire distributed to 102 respondents who had bought Bear Brand milk products. The variables studied include product quality (X1), brand image (X2), and purchase decision (Y). The data analysis technique uses multiple linear regression. The results of the study show that product quality has a positive but not significant influence on purchase decisions, while brand image has a positive and significant influence. This indicates that although consumers are satisfied with the quality of Bear Brand dairy products, a strong brand image is the main factor influencing the purchase decision. Therefore, companies are advised to continue to improve product quality and strengthen brand image through effective marketing strategies.